Pemberdayaan Komunitas Wanita Tani dalam Mendukung Desa Songgon sebagai Sentra Durian di Kabupaten Banyuwangi - Dwi Erwin Kusbianto; Hasbi Mubarak Suud; Subhan Arif Budiman; Ika Purnamasari; M Rondhi; Ebban Bagus Kuntadi; Rokhani Rokhani (Institut Pertanian Bogor, 2025)
Songgon is known as a favorite durian-producing village in Banyuwangi Regency. However, in the last 3 years, durian farmers have been suffering because they failed to experience a bumper harvest. The purpose of this service is to initiate the restoration of the image of Songgon Village as the center of Banyuwangi durian through the provision of quality local Songgon durian seeds. The partner of this community service is the wives of farmers in the village or also called Wanita Tani. Community service methods was using counseling and educational methods, along with training in seedling cultivation skills, followed by assistance in seedling care. A series of activities carried out include: 1) Increasing financial literacy to Women Farmers so that in the future they can face crises if crop failure recurs in the future; 2) Empowerment of farm women in terms of producing rootstocks (durian seedlings from seeds) for side income of Farm Women during the service activities; 3) Grafting training with rootstocks that have been produced and the scion comes from the local durian of each farmer's garden; The results of the activity are introduction people about financial literacy for the target group; Increased skills in the form of the ability to produce seeds independently; As well as the formation of a community with one of the inventories in the form of a planting hole maker that can be rented out to durian farmers in Songgon Village. However, this service has not been able to increase the income of farm women directly because there has been no sale of the seeds produced, but institutional initiation in marketing seeds has been carried out.